Functional movement screen for predicting running injuries in 18- to 24-year-old competitive male runners - Hotta, T.; Nishiguchi, S.; Fukutani, N.; Tashiro, Y.; Adachi, D.; Morino, S.; Shirooka, H.; Nozaki, Y.; Hirata, H.; Yamaguchi, M.; Aoyama, T. (The Journal of Strength and Conditioning Research, 2015)
The purpose of this study was to investigate whether the functional movement screen (FMS) could predict running injuries in competitive runners. Eighty-four competitive male runners (average age = 20.0 ± 1.1 years) participated. Each subject performed the FMS, which consisted of 7 movement tests (each score range: 0-3, total score range: 0-21), during the preseason. The incidence of running injuries (time lost because of injury = 4 weeks) was investigated through a follow-up survey during the 6-month season. Mann-Whitney U-tests were used to investigate which movement tests were significantly associated with running injuries. The receiver-operator characteristic (ROC) analysis was used to determine the cutoff. The mean FMS composite score was 14.1 ± 2.3. The ROC analysis determined the cutoff at 14/15 (sensitivity = 0.73, specificity = 0.54), suggesting that the composite score had a low predictability for running injuries. However, the total scores (0-6) from the deep squat (DS) and active straight leg raise (ASLR) tests (DS and ASLR), which were significant with the U-test, had relatively high predictability at the cutoff of 3/4 (sensitivity = 0.73, specificity = 0.74). Furthermore, the multivariate logistic regression analysis revealed that the DS and ASLR scores of =3 significantly influenced the incidence of running injuries after adjusting for subjects' characteristics (odds ratio = 9.7, 95% confidence interval = 2.1-44.4). Thus, the current study identified the DS and ASLR score as a more effective method than the composite score to screen the risk of running injuries in competitive male runners.